PERTANGGUNGJAWABAN PIDANA TERHADAP PELAKU TINDAK PIDANA PEMILU LEGISLATIF TAHUN 2014 (Studi Putusan Nomor: 70/Pid./2014/PT.TJK.) - Selvi Yuliyanti (Universitas Lampung, 2016)
The criminal responsibility of the perpetrators of criminal acts of legislative elections in 2014 in Decision No. 70/Pid./2014/PT.TJK based on the presence of errors and intentional element in the commission of a crime, the defendant's ability to be responsible, there is no justification and forgiving for the defendant in committing criminal offenses legislative elections, by deliberately adding voice to a certain election participants. The judges convict the Defendants therefore with imprisonment for 3 (three) months, and a fine IDR 500.000 (five hundred thousand rupiah) provided that if the fine is not paid then replaced with imprisonment for 1 (one) month. Basic legal considerations judges in imposing criminal offense to legislative elections in 2014 juridically is the fulfillment of the evidence in the trial referred to in Article 183 and Article 184 Criminal Procedure Code. Philosophically considered that the criminal as a guidance to the behavior of the accused. Sociologically consists of aggravating factors, namely the defendant as the election organizer has injured the implementation of democracy and the mitigating circumstances that the defendants confessed and has not been convicted, have family responsibilities and polite during the trial. Keywords: Criminal Liability, Election, Legislative